Implementing Mobile HRV Biofeedback as Adjunctive Therapy During Inpatient Psychiatric Rehabilitation Facilitates Recovery of Depressive Symptoms and Enhances Autonomic Functioning Short-Term: A 1-Year Pre–Post-intervention Follow-Up Pilot Study - Tatschl, Josef M.; Hochfellner, Sigurd M.; Schwerdtfeger, Andreas R. (Frontiers in Neuroscience, 2020)
Objective: New treatment options for depression are warranted, due to high recurrence rates. Recent research indicates benefits of heart rate variability biofeedback (HRVBF), on symptom recovery and autonomic functioning in depressed individuals. Deep breathing induced amplification of vagus nerve activity is the main element of HRVBF. Thus, the latter represents a safe and non-invasive complementary depression treatment. However, its efficacy in patients undergoing inpatient psychiatric rehabilitation receiving highly comprehensive treatments, has not been evaluated. Methods: Ninety-two inpatients were randomly assigned to an intervention group (IG) or control (CG) group. While the latter received the standard treatment only, adjunctive HRVBF was provided to the IG over five weeks. Depression severity and heart rate variability (HRV) were assessed before (pre) and after the five weeks (post). Moreover, one year-follow-up depression scores were available for 30 participants. Results: Although depression improved in both groups, the IG exhibited significantly larger improvements at post-assessment (np 2 = .065) and significant increases in LF-HRV (d = .45) and cardio-respiratory coherence (d = .61). While the IG exhibited significantly lower depression scores at post-assessment (p = .042, d = .79), this effect decreased during follow-up (p = .195, d = .48). Conclusion: HRVBF improved autonomic functioning and facilitated depression recovery during inpatient psychiatric rehabilitation, emphasizing its value as adjunctive therapy regardless of concurrent treatments. Moreover, these incremental benefits could serve as resource even after the actual training period. However, the additional antidepressant gains vanish during the long-term follow-up, indicating the need for more intense training or regular practice afterwards, respectively. Thus, future studies are warranted to examine how the initial benefits of HRVBF during inpatient psychiatric rehabilitation can be preserved post discharge.